![image](https://tex.z-dn.net/?f=2%5Ccdot+6%5E%7Bx%7D-24%5E%7Bx%7D-9%5Ccdot+4%5E%7Bx%2B1%7D%2B72%3D0%5C%5C%5C%5C2%5Ccdot+6%5E%7Bx%7D-6%5E%7Bx%7D%5Ccdot+4%5E%7Bx%7D-9%5Ccdot+4%5E%7Bx%7D%5Ccdot+4%2B72%3D0%5C%5C%5C%5C6%5E%7Bx%7D%282-4%5E%7Bx%7D%29%2B9%5Ccdot+4%282-4%5E%7Bx%7D%29%3D0%5C%5C%5C%5C%282-4%5E%7Bx%7D%29%286%5E%7Bx%7D%2B36%29%3D0%5C%5C%5C%5C1%29%5C%3B+2-4%5E%7Bx%7D%3D0%2C%5C%3B+%5C%3B+4%5E%7Bx%7D%3D2%2C%5C%3B+2%5E%7B2x%7D%3D2%2C%5C%3B+%5Cto+%5C%3B+2x%3D1%2C%5C%3B+x%3D%5Cfrac%7B1%7D%7B2%7D%5C%5C%5C%5C2%29%5C%3B+6%5E%7Bx%7D%2B36%3D0%2C%5C%3B+6%5E%7Bx%7D%3D-36%5C%3B+net%5C%3B+reshenij%2Ct.k.%5C%3B+6%5E%7Bx%7D%3E0)
0" alt="2\cdot 6^{x}-24^{x}-9\cdot 4^{x+1}+72=0\\\\2\cdot 6^{x}-6^{x}\cdot 4^{x}-9\cdot 4^{x}\cdot 4+72=0\\\\6^{x}(2-4^{x})+9\cdot 4(2-4^{x})=0\\\\(2-4^{x})(6^{x}+36)=0\\\\1)\; 2-4^{x}=0,\; \; 4^{x}=2,\; 2^{2x}=2,\; \to \; 2x=1,\; x=\frac{1}{2}\\\\2)\; 6^{x}+36=0,\; 6^{x}=-36\; net\; reshenij,t.k.\; 6^{x}>0" align="absmiddle" class="latex-formula">